Penerapan Blended Learning Untuk Meningkatkan Pemahaman Mahasiswa Dalam Pembelajaran Algoritma Pemrograman - Ega Trianingsih Aksana; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Abstract.Blended Learning is a combination of face-to-face learning and online learning. In elementary schools, many teachers choose to use blended learning to improve students' understanding, especially in computer subjects in mathematics learning at FITK UIN Sumatra Worodugu. So the aim of this research on the one hand is to encourage the use of integrated learning models for mathematics students to assess the development of students' understanding of programming concepts. This research uses qualitative research and the type of research analyzed is descriptive. Researchers tested students' perceptions of online education. Knowledge-based learning and connected learning environments during the Covid-19 pandemic. The data from this research is intended to be a source of learning algorithms for teachers and students in the mathematics curriculum. The research results show that the success of continuing education depends on two things: If there are less than 20 students, then the course is held as an independent unit. The second way, if the class has more than 20 people, the first week will be taught directly, the second week there will be introductions, including online training via WAG. The use of blended learning methods can increase students' understanding in algorithmic programming courses about the evolution of blended learning and its application. For example, the Internet due to disease. Can improve children's learning and increase their motivation, especially in the field of technology.